Comparison of the effects of two frequencies (15 & 75 Hz) of high voltage pulsed current on blood change in upper extremity of normal subjects - T Motieollah (Babol University of Medical Sciences, 2004)
Background and Objective: Increase in blood flow and tissue temperature is one of the purposes in physical therapy. Recently electrical stimulation has been applied for this situation. This study was performed to compare the effect of two frequencies (15 & 75 Hz) of HVPC on blood change in upper extremity of normal subjects. Methods: This study was performed on 30 subjects (13 males & 17 females) with age range between 21-33 years (Min 24.57±3.46). High voltage pulsed current (HVPC) was applied in cervical area (C7) and skin temperature was recorded pre/during and post stimulation. Statistical methods including F test, Duncan’s new multiple test and Fisher exact test were used for data analysis. Findings: The results showed that both frequencies of HVPC (15 & 75 HZ) increase the skin temperature. In comparison to skin temperature in 75 Hz current was slightly higher (0.3°C) than 15Hz. The difference was not statistically significant. Conclusion: After application of HVPC (340 volt) with two frequencies (15 & 75 Hz) vasodilatation occurs, circulation was improved and increased skin temperature.